Si le das una galletita a un raton - Numeroff, Laura Joffe; Bond, Felicia (New York : HarperCollins Pub., 1995)
A retelling, in Spanish, of If You Give a Mouse a Cookie.
Accelerated Reader
Keywords: Mice -- Fiction; Spanish language -- Reading materials